2007
DOI: 10.1108/00220410710723894
|View full text |Cite
|
Sign up to set email alerts
|

What is enough? Satisficing information needs

Abstract: Purpose -This paper seeks to understand how users know when to stop searching for more information when the information space is so saturated that there is no certainty that the relevant information has been identified. Design/methodology/approach -Faculty, undergraduate and graduate students participated in focus group interviews to investigate what leads them to satisfice their information needs. Findings -Academic library users describe both qualitative and quantitative criteria, which lead them to make rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 19 publications
1
123
0
1
Order By: Relevance
“…Studies such as these may shed additional light on the issues of satisficing, for example (Prabha et al, 2007). Finally, since the affective phenomena tend to be intertwined with cognitive and situational factors, the picture of the motivational aspects of emotions, feelings, mood and affective styles can be deepened by looking at these factors together rather than separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as these may shed additional light on the issues of satisficing, for example (Prabha et al, 2007). Finally, since the affective phenomena tend to be intertwined with cognitive and situational factors, the picture of the motivational aspects of emotions, feelings, mood and affective styles can be deepened by looking at these factors together rather than separately.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of work-related information seeking, the constraining role of negative emotions and feelings has often been conceptualized in terms of satisficing -a portmanteau combining the words satisfying and sufficing, coined by Herbert Simon to describe a decision-making strategy that attempts to meet criteria for adequacy, rather than identify an optimal solution, especially when time is a critical variable (Prabha, Connaway, Olszewski, & Jenkins, 2007). The main question dealing with satisficing behaviors revolves around "what is enough" in information seeking.…”
Section: Limiting and Terminating The Information-seeking Processmentioning
confidence: 99%
“…Similarly, Zack (2004) reports on the activities of arts administrators in information seeking, focusing particularly on their approach of stopping when they have sufficient information for the task at hand. Prabha et al (2007) develop an account of satisficing in information seeking based on role theory and rational choice theory. A common feature of all these studies is that they focus on the stopping criterion (when is enough enough?…”
Section: Discussionmentioning
confidence: 99%
“…Thus the amount of information that creates a 'satisfaction' level (satisfices) is situation specific (Simon, 1956). Dissatisfaction is multi-faceted with 'inconvenience', 'not enough information', and 'search is too difficult' (all these aspects found elsewhere (Prabha et al, 2007)). Satisfaction then is a dynamic, situation-specific component that determines the stopping point of the search process.…”
mentioning
confidence: 99%
“…Logically, studies of information seeking may include elements of searching as indicated in Wilson's (1999) nested model. Student information seeking has often been described in terms of comfort or convenience (MacDonald et al (2011);Prabha et al (2007) ; Zach (2005).Models of information seeking behaviour among students include a model of the mediating factors that influenced student use of electronic information services (in particular) (Urquhart and Rowley, 2007). The specific (micro) factors were information literacy (defined in terms of skills and knowledge that students could bring to searching), searching strategies (the type of searching routines normally adopted), academics' information behaviour (and their influence as role models for students), discipline, pedagogy (approach adopted to learning and teaching), and support and training (provided partly by library services, perhaps acting in co-operation with academic staff).…”
mentioning
confidence: 99%